Prevalencia de anemia en parasitosis intestinal y su relación con el grupo socioeconómico, en la Escuela Fiscal Mixta Dr. Luis Poveda Orellana. Parroquia El Progreso. Pasaje. El Oro. 2014. - Morocho Rivera, Ronald Humberto (2015)
This research was observational, analytical, cross-sectional non-experimental design it was made in the months of June and July 2014. The objective was to determine the prevalence of anemia in school children with intestinal parasitosis in the parish of Canton Pasaje El Progreso 139 students of the Fiscal school Dr. "Luis Poveda Orellana" whom I was asked one to three samples for coproparasitario and who had intestinal parasitosis are to take the blood sample for CBC and has studied applied modified survey socioeconomic stratification prevalence of intestinal parasitosis 70.50% and 29.50% was reported as being negative histolytica amoeba the increased presence of the 54.08% they were male and 45.92% was demonstrated They were women.